SEMANTIC FEATURES OF EUPHEMISMS RELATED TO ECOLOGY, ENERGY, AND TECHNOLOGY IN GERMAN MEDIA DISCOURSE - Nurqulov Javlon Rashid o’g’li (International Journal of Literature and Language Studies, 2026)
In this article, the author provides a semantic analysis of euphemisms related to ecology, energy, and technology in German media discourse based on materials from newspapers and magazines.